Special educational needs, inclusion, and diversity - Frederickson, Norah; Cline, Tony (McGraw Hill Education/Open University Press, 2015)
Special Educational Needs, Inclusion and Diversity 3E has established itself as the textbook on special educational needs (SEN). The new edition of this popular textbook retains its comprehensive, insightful and accessible approach and reflects the latest changes in policy and legislation. It provides a stimulating balance between theory, research and practice as well as a unique analysis of the implications for SEN of linguistic, cultural and ethnic diversity. Recognizing the complex and difficult nature of many special educational needs, the authors place a firm emphasis on inclusion and suggest practical strategies enabling professionals to maximise inclusion while at the same time recognizing and supporting diversity.